Drug Carriers - Jesús Villarreal-Gómez, Luis (IntechOpen, 2022)
Conventional drug administration has several issues and challenges. Drugs may not be fully absorbed or targeted, some drugs produce undesirable secondary effects and cause organ damage, and others trigger inflammation and immune response. As such, drug carrier systems are being developed to help promote drug absorption, enhance targeting, and avoid or decrease negative symptoms. This book examines different drug carriers and drug carrier systems. Chapters address such topics as the use of polymers in drug carrier systems, thin films, metal-organic frameworks, graphene quantum dots, and nanotechnology and microfluidics for drug delivery.